Conceptualizing and experiencing compassion - Condon, Paul (2013)
Does compassion feel pleasant or unpleasant? People tend to categorize compassion as a pleasant or positive emotion, but laboratory compassion inductions, which present another’s suffering, may elicit unpleasant feelings. Across two studies, we examined whether prototypical conceptualizations of compassion (as pleasant) differ from experiences of compassion (as unpleasant). Following laboratory-based neutral or compassion inductions, participants made abstract judgments about compassion relative to various emotion-related adjectives, thereby providing a prototypical conceptualization of compassion. Participants also rated their own affective states, thereby indicating experiences of compassion. Conceptualizations of compassion were pleasant across neutral and compassion inductions. Following exposure to others’ suffering, however, participants felt increased levels of compassion and unpleasant affect, but not pleasant affect. Following neutral inductions, participants reported more pleasant than unpleasant affect, with moderate levels of compassion. Thus, prototypical conceptualizations of compassion are pleasant, but experiences of compassion can feel pleasant or unpleasant. The implications for emotion theory in general are discussed.